The role of special economic zones in improving effectiveness of Greater Mekong Subregion economic corridors. (Metro Manila, Philippines Asian Development Bank, 2018)
This study looks into the role of special economic zones in strengthening competitiveness of economic corridors in the Greater Mekong Subregion. It examines factors behind the success of special economic zones and the role they can play in Greater Mekong Subregion (GMS) economic corridor development. The analysis is based on a company level survey in the Mae Sot special economic zone and interviews with clients operating in other zones throughout the GMS. The report offers policy recommendations for GMS ministers on how the zones can contribute toward improving competitiveness of economic corridors and thereby promote economic development.
Keywords: Industry and state -- Asia; Economic development -- Asia; Electronic books